Improving thermal conductivity of fired clay brick using sawdust waste - Deraman, Rafikullah; Abdullah, Abd Halid bin; Nagapan, Sasitharan; Abas, Nor Haslinda; Suratkon, Azeanita Binti; Hasmori, Mohd Fikri (Politeknik Malaysia, 2018)
The demand for energy efficient design and construction has become progressively important with the growing energy costs and increasing awareness on the effects of global warming. Global warming causes a higher temperature of the surrounding, which will give significant effect to the energy consumption in commercial and residential building. Therefore, this study aims to investigate the possibility of incorporating sawdust as an additive material to improve thermal insulation properties of clay brick through lowering its thermal conductivity value. This study uses three types of soils with the proportion of clay soil (80%), laterite soil (10%) and grey soil (10%). The percentages of sawdust waste used as an additive are 2.5%, 5% and 7.5% by weight. The laboratory works performed involve the geotechnical gradation, physical, mechanical, chemical composition and thermal conductivity of fired clay brick. There are two types of brick that were produced in this study, which are control brick (CB) and sawdust brick (SB). The results show that the thermal conductivity of fire clay brick improves with the increasing percentage of waste material. Therefore, in this study, it appears that the brick incorporated with 5% of the sawdust waste is the optimum value that can achieve 7.5 MPa of compressive strength, 23.01.56% of water absorption and 0.384 W/m˚C of thermal conductivity. Thus, 5% of sawdust waste is chosen as the optimum percentage that yields better fired clay brick. This study reveals that the sawdust is a potential waste material that can be used to improve the thermal property and as a sustainable construction material.